Perlindungan Hukum dan Peningkatan Kualitas Pekerja Tenun Kain Endek/Songket di Desa Gelgel Kabupaten Klungkung - Ni Komang Arini Styawati; I Made Mardika; Ida Ayu Putu Widiati (Universitas Warmadewa, 2022)
Gelgel Village is one of the villages in the Klungkung District, Klungkung Regency, Bali Province. Gelgel village is famous for the production of Balinese woven fabrics, namely songket and endek. Songket/endek cloth is one of the characteristics of Balinese cultural products. In the past, Balinese endek/songket fabrics were very famous, not only in demand by domestic tourists, but also in demand by foreign tourists. However, in its development endek fabric has decreased, this can be seen from the decreasing production of songket/endek woven fabrics, as a result of competition with similar fabrics produced by factories that enter the market. The obstacle faced by Partners is the competition for endek/songket woven fabrics at lower prices. Partners also experience problems in the production process of songket/endek fabrics, which are constrained by the limited number of workers as pattern/design makers. The development of songket/endek fabric production has also experienced a very drastic decline with the Covid-19 pandemic, this has an impact on the production of songket/endek woven fabrics and also has an impact on the fate of weaving workers in Gelgel Village, Klungkung Regency. Therefore. This PKM seeks to empower weaver groups, namely in the form of legal protection and increasing the production of songket/endek fabrics in Gelgel Village, Klungkung.